Women’s Participation in Freedom Movement in Princely Mysore with Special Reference to Gandhian Ideologists - Sonia M.V. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This article examines women’s participation in the freedom movement in Princely Mysore, with a special focus on the influence of Gandhian ideology. While the Mysore state, ruled by the Wodeyars, was considered “Modern Mysore” with administrative progress, it also faced suppression of aspirations for Responsible Government. The national movement, spearheaded by organizations like the Mysore State Congress (established 1938), drew significant involvement from women, many encouraged by their families. Women like Subbamma Jois, Yashodhara Dasappa, Caveramma, and Chennamma were prominent. Their activities included Khadi production and promotion (e.g., at the Badnaval center), picketing liquor shops, and civil disobedience, leading to arrests and imprisonment. These actions demonstrated a strong nationalistic urge and a commitment to Gandhian principles of simplicity and self-sacrifice, ultimately contributing to the state’s merger with independent India.